Effect of ultraviolet and moisture action on biodegradable polymers and their blend. (June 2020) - Mistretta, Maria Chiara; La Mantia, Francesco Paolo; Titone, Vincenzo; Botta, Luigi; Pedeferri, Mariapia; Morreale, Marco
In this work, the suitability of polylactic acid (PLA), polybutylene adipate terephthalate (PBAT) and PBAT/PLA blend samples to outdoor applications were investigated in terms of mechanical, morphological and visual properties in presence of ultraviolet action and water, finding that PLA in particular can be actually considered for such applications.